Dominants of the scientific and linguistic world of Anatolii Moisiienko - Бойко, Надія (Київський національний університет імені Тараса Шевченка, 2023)
The analysis of scientific & linguistics dominants of A. Moisiienko revealed the synthesis of the fundamental knowledge of a linguist and literary critic, the dynamics of emotions, and the expression of the poet’s evaluations aimed at updating the national scientific and artistic paradigms. The linguist managed to combine several hypostases, appearing before the reader as a scrupulous linguist-researcher of the apperceptive system of Shevchenko’s poem, the worlds of symbols and the silent word, the world of poetics and the dynamics of text structures, the world of the intertextuality of the poetic text; and as an obsessed literary critic who, raising several extremely relevant problems of the modern scientific study of poetic idiostyles, specific features of individual authorial verse genres in the system of individual artistic texts, focuses on European intellectualism and modernism; and as an inspired poet, in whose poems the Ukrainian poetic language appears as a world of linguistic and aesthetic signs of national culture. The scientific texts of A. Moisiienko were studied from the standpoint of anthropocentrism and textocentrism, considering the structure of textual categories, means of their objectification, and factors of actualization of the author’s dominant constants. The multi-aspect studies of A. Moisiienko’s poetic linguistics are commented on, which gives an idea of the specificity of the figurative idiopoetic system, and its dominant features, which distinguish the author's language creation against the all-Ukrainian background and among traditional samples of national poetics. It was found that the dominant features of the author’s scientific linguistic world include the linguistic stylistic interpretation of the apperceptive system of Shevchenko’s poem, the artistic understanding of the linguistic worlds of symbol and silent word, the world of poetics and the dynamics of text structures, the world of the intertextuality of a poetic text.

Досліджено наукові тексти А. Мойсієнка з позицій антропоцентризму, текстоцентризму, з урахуванням структури текстових категорій, засобів їхньої об’єктивації, чинників актуалізації авторських домінантних констант. Прокоментовано різноаспектні дослідження поетичного мовосвіту А. Мойсієнка, що дає уявлення про специфічність образної ідіопоетичної системи, її домінантних рис, які вирізняють мовотворчість автора на загальноукраїнському тлі та з-поміж традиційних зразків національної поетики. З’ясовано, що до домінантних рис наукового мовосвіту автора належить лінгвостилістична інтерпретація аперцепційної системи Шевченкового вірша, художнє осмислення мовосвітів символу й онімного слова, світу поетики й динаміки текстових структур, світу інтертекстуальності поетичного тексту.
Домінанти наукового мовосвіту Анатолія Мойсієнка
Keywords: мовосвіт; аперцепційна система Шевченкового вірша; світ символу; світ онімного слова; світ поетики й динаміки текстових структур; світ інтертекстуальності; Анатолій Мойсієнко; world of language; apperceptive system of Shevchenko’s poem; world of symbol; world of silent word; world of poetics and dynamics of text structures; world of intertextuality; Anatolii Moisiienko